2010
DOI: 10.1007/s12032-010-9512-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy use and risk of bone marrow suppression in a large population-based cohort of older women with breast and ovarian cancer

Abstract: We studied 65,521 women with breast cancer and 7,420 women with ovarian cancer aged ≥ 65 identified from the 16 areas of the Surveillance, Epidemiology and End Results program linked with Medicare data during 1991-2002. Bone marrow toxicity associated with chemotherapy was defined using diagnosis codes from Medicare inpatient, outpatient and physician claims. The time to event Cox regression was utilized to estimate the risk of bone marrow toxicity. Use of anthracyclines, taxanes or platinums was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 26 publications
2
47
1
Order By: Relevance
“…Together, these results suggest that CEF treatment caused bone marrow suppression and adipocyte expansion without affecting adipocyte differentiation. The finding of reduced bone marrow cellularity is in agreement with clinical studies which indicate a dose-response relationship between administration of anthracycline-based regimens and risk of bone marrow suppression in breast cancer patients, and a direct association between the number of treatment cycles and bone marrow toxicity [8]. Fat cells occupying haematopoietic marrow following chemotherapy is a common diagnostic feature in patients receiving chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Together, these results suggest that CEF treatment caused bone marrow suppression and adipocyte expansion without affecting adipocyte differentiation. The finding of reduced bone marrow cellularity is in agreement with clinical studies which indicate a dose-response relationship between administration of anthracycline-based regimens and risk of bone marrow suppression in breast cancer patients, and a direct association between the number of treatment cycles and bone marrow toxicity [8]. Fat cells occupying haematopoietic marrow following chemotherapy is a common diagnostic feature in patients receiving chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from the indirect adverse effects on bone, bone marrow toxicity is also commonly reported in breast cancer survivors. A recent population-based observational study found a dose-response relationship between administrations of anthracycline-based regimens and a risk of bone marrow suppression in those with breast cancer, with possible irreversible loss of bone marrow function from non-cell-cycle dependent drugs such as alkylating agents and anthracyclines [8]. Clinically, patients receiving chemotherapy and irradiation treatment have also been reported to have an increased marrow fat content [9].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased BMSCs, which include mesenchymal stem cells and hematopoietic stem cells, are cause of myelosuppression that not only limits the treatments but also is a risk factor for poor prognosis, as it substantially diminishes the immunity [14,15]. Consistent with previous reports that Dox causes myelosuppression [16,17], we found Dox significantly decreased the numbers of BMSCs of tumor-bearing mice either in 6-days or in 42-days treatments [1].…”
supporting
confidence: 88%
“…Unfortunately, despite the clinical benefits of DOX, its use is often limited by serious adverse effects, such as severe cardiotoxicity and myelosuppression [5,9,10]. Severe dose-dependent cardiotoxicity occurs in~50% of patients treated with DOX.…”
Section: Molecular Mechanisms Of Doxorubicin-induced Cardiomyopathymentioning
confidence: 99%